« La quadrature du cercle » des législations sur la prostitution en Grèce dans une perspective comparatiste - Yagos Koliopanos; Alexia Sarantopoulou (Genre, Sexualité et Société)
Given the fact that the conception and the application of Greek law regarding prostitution are rooted in a long tradition of regulation, our article attempts an analysis of the current prostitution policies in Greece through the lens of gender and sexuality norms. What emerges is that these policies represent a specific model of « neo-reglementarism » which conserves the hygienist, carceral and masculinist aspects of the old regime. Through a comparison with the respective legislation and policies in France, we have observed a convergence of their principal goals, which are the invisibilisation of prostitution and the removal of illegal migrant individuals. Those goals remain at the heart of an international legislation aiming at fighting sex trafficking. In the Greek context, this legislation creates a particular scenery where “neo-reglementarist” and “neo-abolitionist” ideologies come to clash with one another.